Carbon Dot based Fluorescence sensor for Retinoic acid. Issue 2 (15th January 2018) - Majumdar, Sristi; Bhattacharjee, Tuhin; Thakur, Debajit; Chowdhury, Devasish
Abstract: In this work chitosan carbon dot (chiCD) based fluorescence sensor was developed which can selectively detect Retinoic acid (RA). The CDs were prepared from chitosan hydrogel and further conjugated with NaF to develop a chiCD‐NaF system for the detection of Retinoic acid based on its PL properties. It was found that addition of NaF resulted in the enhancement of fluorescent spectra of ChiCD. Addition of RA to the chiCD‐NaF system resulted in quenching of the PL spectra. The detection of RA was selective as there is no change in PL properties using other vitamins viz. ascorbic acid, choelcalciferol, Folic acid, Riboflavin, Tocopherol etc. The chiCD‐NaF systems were also checked with two commercially available capsule containing mixtures of vitamins and here too PL change was insignificant demonstrating selectivity of RA. A probable mechanistic behaviour of the system towards different vitamins is also explained in this paper. Abstract : We develop a fluorescence based method using chitosan carbon dot‐NaF which can selectively detect Retinoic Acid. The CDs were prepared from chitosan hydrogel and further conjugated with NaF to develop a chiCD‐NaF system for the detection of Retinoic acid based on its PL properties. It was found that addition of NaF resulted in the enhancement of fluorescent spectra of ChiCD. Addition of RA to the chiCD‐NaF system resulted in quenching of the PL spectra.